Розробка користувацького інтерфейсу для веб-сайту - Дудник, Д. А. (ХНУРЕ, 2024)
This article allows you to consider a wide range of web design aspects and explore their impact on creating an effective interface for websites, while ensuring relevance and interest for modern requirements in the online environment.
Keywords: користувацький інтерфейс; інтерфейс для веб-сайту